2007
DOI: 10.1016/j.rmed.2006.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Increased myocardial vulnerability and autonomic nervous system imbalance in obstructive sleep apnea syndrome

Abstract: OSAS is associated with a significant worsening in HRV, HRT, and QT dynamicity parameters. Our results may indicate that HRV and QT dynamicity parameters can be useful noninvasive methods that may detect autonomic nervous system activity and ventricular vulnerability in OSAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 24 publications
0
52
0
2
Order By: Relevance
“…Furthermore, in patients with OSA, QT dynamicity, a marker of augmented myocardial vulnerability to arrhythmias, has been found to be related to the severity of AHI [86].…”
Section: Observational Studiesmentioning
confidence: 99%
“…Furthermore, in patients with OSA, QT dynamicity, a marker of augmented myocardial vulnerability to arrhythmias, has been found to be related to the severity of AHI [86].…”
Section: Observational Studiesmentioning
confidence: 99%
“…Ari et al 19 reported that HRT worsened in OSA while HRV did not change and there was a relationship between HRT and AHI. Aytemir et al 20 observed increased myocardial vulnerability and autonomic nervous system imbalance in OSA cases. They found that HRT, HRV and QT dynamicity parameters were significantly worse among patients with OSA.…”
Section: Discussionmentioning
confidence: 98%
“…[19][20][21][24][25][26][27] The authors of these studies thought that this deterioration might be due to hypoxia during periods of apnea. Ari et al 19 reported that HRT worsened in OSA while HRV did not change and there was a relationship between HRT and AHI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms by which OSA affects the cardiovascular system may involve mechanical effects on intrathoracic pressure, sympathetic overstimulation, intermittent hypoxia, oxidative stress, inflammation, hyper coagulation, metabolic dysregulation and endothelial dysfunction (3,5). The repetitive respiratory events cause hypoxia, hypercapnea, arousals, or disrupted sleep singly or in combination (6)(7)(8)(9)(10). These abnormal physiologic events result in increased sympathetic outflow and alterations in blood pressure control mechanisms.…”
Section: Introductionmentioning
confidence: 99%